2023
DOI: 10.3390/ijms24065155
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Imaging of Coronary Atherosclerotic Plaque: From Assessment of Pathophysiological Mechanisms to Therapeutic Implication

Abstract: Atherosclerotic cardiovascular disease is the leading cause of morbidity and mortality worldwide. Several cardiovascular risk factors are implicated in atherosclerotic plaque promotion and progression and are responsible for the clinical manifestations of coronary artery disease (CAD), ranging from chronic to acute coronary syndromes and sudden coronary death. The advent of intravascular imaging (IVI), including intravascular ultrasound, optical coherence tomography and near-infrared diffuse reflectance spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 129 publications
0
13
0
Order By: Relevance
“…Stent expansion is the process of deploying the stent to achieve a desired vessel diameter based on reference vessel size, ensuring adequate luminal gain and restoration of blood flow, and decreasing risk of in-stent restenosis [58][59][60][61] . Generally, moderate stent under expansion refers to a stent-to-artery ratio less than 90% while (Adapted from Gurgoglione et al [53] under Creative Commons License). OCT: optical coherence tomography; IVUS: intravascular ultrasound.…”
Section: Evaluation Of Stent Apposition Expansion and Post-pci Compli...mentioning
confidence: 99%
See 3 more Smart Citations
“…Stent expansion is the process of deploying the stent to achieve a desired vessel diameter based on reference vessel size, ensuring adequate luminal gain and restoration of blood flow, and decreasing risk of in-stent restenosis [58][59][60][61] . Generally, moderate stent under expansion refers to a stent-to-artery ratio less than 90% while (Adapted from Gurgoglione et al [53] under Creative Commons License). OCT: optical coherence tomography; IVUS: intravascular ultrasound.…”
Section: Evaluation Of Stent Apposition Expansion and Post-pci Compli...mentioning
confidence: 99%
“…OCT offers superior resolution for detecting and characterizing edge dissections, including their length, depth, and location in relation to the stent struts. Due to the high-resolution images produced by OCT, this (Adapted from Gurgoglione et al [53] under Creative Commons License). OCT: optical coherence tomography.…”
Section: Evaluation Of Stent Apposition Expansion and Post-pci Compli...mentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathological studies found pronounced adventitial pro-inflammatory milieu at the site of coronary vasospasm, with increased levels of eosinophils and neutrophils cells [ 47 , 48 ]. Intracoronary imaging tools, traditionally used to characterize coronary plaque phenotype and to guide percutaneous coronary interventions (PCI) [ 49 ], have contributed to understand CAS pathology: studies with intravascular ultrasound and optical coherence tomography revealed diffuse intimal thickening [ 50 ], as well as abundant macrophages and an exaggerated expression of vasa vasorum at spastic sites [ 51 ]. Importantly, by leveraging 18-fluorodeoxyglucose positron emission tomography/computed tomography, Ohyama et al found a close link between the expansion of perivascular and pericoronary adipose tissue and the susceptibility to CVD [ 52 ].…”
Section: Pathophysiologymentioning
confidence: 99%